2015
DOI: 10.1007/s10689-015-9818-8
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of paraganglioma/pheochromocytoma and papillary thyroid carcinoma: a four-case series analysis

Abstract: The paraganglioma (PGL)/pheochromocytoma (PHEO)-papillary thyroid carcinoma (PTC) dyad has been reported rarely. Whether the association is coincidental or results from an underlying genetic predisposition is difficult to ascertain. We analyzed clinical and molecular data on four unrelated patients identified and treated by one of us (MJB) at a tertiary center. Patients were screened for germline variants in a panel of candidate genes: RET, VHL, SDHB, SDHC, SDHD, SDHAF2, TMEM127, MAX, PTEN, CDKN1B. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…Catecholamine hypersecretion can be occasionally detected in malignant paraganglioma, defined by distant metastases or extensive local invasion into adjacent tissue ( 20 ). However, as reported in the present study and previous literature ( 4 – 6 ), the levels of catecholamine were not increased in TP, which can be differentiated from other paragangliomas. Similarly, a correct diagnosis could not be established preoperatively by FNAB, except for by immunohistochemistry, until the introduction of the novel method using cell block material ( 21 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Catecholamine hypersecretion can be occasionally detected in malignant paraganglioma, defined by distant metastases or extensive local invasion into adjacent tissue ( 20 ). However, as reported in the present study and previous literature ( 4 – 6 ), the levels of catecholamine were not increased in TP, which can be differentiated from other paragangliomas. Similarly, a correct diagnosis could not be established preoperatively by FNAB, except for by immunohistochemistry, until the introduction of the novel method using cell block material ( 21 ).…”
Section: Discussionsupporting
confidence: 82%
“…The diagnosis of TP is challenging, not due to its low prevalence (only 60 cases have been reported), but the cytologic and histopathologic similarities with other thyroid tumors, such as medullary thyroid carcinoma (MTC) ( 4 , 5 ). The examination of immunohistochemical staining serves an important role in the definitive diagnosis; however, to the best of our knowledge, the malignant potential of TP remains unknown ( 3 , 6 , 7 ). Since it was described by Van Miert ( 8 ) in 1964, TP has been commonly considered to have low malignant potential ( 1 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…MEN is characterized by thyroid, adrenal medulla, and parathyroid neuro-endocrine cell proliferation or tumor, and the clinical manifestations are MTC, PHEO, and primary parathyroid primary hyperparathyroidism[5,6]. A few cases were reported to exhibit combinations of PHEO, abdominal paraganglioma, and papillary thyroid carcinoma[7,8]. However, the coexistence of head and neck paraganglioma and papillary thyroid carcinoma was extremely rare and only reported in three cases (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…From our review of literature of the studies found with simultaneous pheochromocytoma/paraganglioma and papillary thyroid carcinoma, the most comprehensive one was a four-case series analysis. It consisted of four female patients, one of them with synchronous PTC and PGL; 2 had heterozygous germline variants in SDHB and the four of them had -79 T>C CDKN1B gene polymorphism (3 homozygous and 1 in heterozygous state) [ 6 ]. This gene is not routinely tested in the panel for pheochromocytoma [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%